2011
DOI: 10.1016/j.fertnstert.2011.01.137
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise in women with polycystic ovary syndrome improves ovarian morphology independent of changes in body composition

Abstract: In a prospective study, 8 women with polycystic ovary syndrome completed 16 weeks of individualized aerobic exercise training. Independent of changes in body weight and adiposity there was a significant increase in aerobic fitness and insulin sensitivity and a significant decrease in the total number of follicles measured by magnetic resonance imaging.Recently and based initially on studies in obesity and type 2 diabetes, lifestyle modification has been adopted as the first line of treatment to manage both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 29 publications
2
29
0
1
Order By: Relevance
“…Additionally, menstrual cycle improvements have been shown following exercise intervention in women with PCOS 19, 36, 40 . Though some studies show reductions in body weight with exercise 19, 20, 36 , several studies have shown that benefits occur without weight loss 28, 37, 41 and suggest that exercise for PCOS would be recommended even if weight loss were not achieved. Our study showed improvements in insulin resistance as measured by euglycemic-hyperinsulinemic clamps (Table 1) and improvements in menstrual function 28 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, menstrual cycle improvements have been shown following exercise intervention in women with PCOS 19, 36, 40 . Though some studies show reductions in body weight with exercise 19, 20, 36 , several studies have shown that benefits occur without weight loss 28, 37, 41 and suggest that exercise for PCOS would be recommended even if weight loss were not achieved. Our study showed improvements in insulin resistance as measured by euglycemic-hyperinsulinemic clamps (Table 1) and improvements in menstrual function 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Though some studies show reductions in body weight with exercise 19, 20, 36 , several studies have shown that benefits occur without weight loss 28, 37, 41 and suggest that exercise for PCOS would be recommended even if weight loss were not achieved. Our study showed improvements in insulin resistance as measured by euglycemic-hyperinsulinemic clamps (Table 1) and improvements in menstrual function 28 . However, despite all these benefits of exercise, few studies have investigated molecular targets in the adipose tissue from women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exercise is a crucial component of lifestyle intervention by promoting several benefits on body composition [2][3][4][5], cardiovascular [2][3][4]6], metabolic [3,[5][6][7][8], reproductive [9][10][11][12] and psychological [13,14] health of women with PCOS. However, the long-term adherence to exercise is a challenge [15].…”
Section: Introductionmentioning
confidence: 99%